Microrna profiling in South African individuals with hypertension and absolute blood pressure levels - Matshazi, Don Makwakiwe (Cape Peninsula University of Technology, 2020)
Background: Hypertension (HPT) is a complex, genetic and environmental condition characterised by sustained high blood pressure and a late presentation of symptoms. It is the single most important modifiable risk factor for cardiovascular diseases (CVDs) and its prevalence and the occurrence of related complications continue to rise in Africa, whilst its magnitude, underlying risk factors and mechanisms remain less understood. Epigenetics offers an avenue to understand the underlying mechanisms, essential in identifying individuals at increased risk of developing HPT, which in turn would facilitate the development of appropriate management strategies. Therefore, we aimed to investigate the microRNA (miRNA) profile in individuals with HPT using next generation sequencing (NGS) for miRNA sequencing as well as quantitative reverse transcription polymerase chain reaction (RT-qPCR). Furthermore, we investigated the functional pathways linked to dysregulated miRNAs in HPT. Methodology: Total RNA was extracted from the whole blood of 573 normotensive, 304 screen-detected hypertensive and 579 known hypertensive male and female participants. Next generation sequencing (NGS) was conducted to screen for differentially expressed miRNAs in a cohort of 48 age-matched normotensive (n=12), screen-detected hypertensive (n=16) and known hypertensive (n=20) females. Findings of the two most differentially expressed miRNAs (miR-30a-5p and miR-1299) in NGS were validated using RT-qPCR in a cohort combining 48 participants from the original NGS investigation and an independent sample of 263 male and female normotensives, screen-detected hypertensives and known hypertensives. Furthermore, in order to identify dysregulated pathways in HPT, Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis was conducted. Using RT-qPCR, the difference in expression of five miRNAs (182-5p, 30a-5p, 30e-3p and 1299 as shown by miRNA sequencing) and miR-126-3p, and their relationship with HPT in 1456 normotensive and hypertensive male and female participants was investigated. The utility of novel miRNAs dysregulated during HPT in predicting clinical blood pressure (BP) parameters was also investigated in normotensive and hypertensive participants. Results: Amongst the dysregulated miRNAs were miR126-3p, 30a-5p, 182-5p, 1299 and 30e-3p and the two novel miRNAs, miR-novel-chr1_36178 and miR-novel-chr15_18383. The dysregulation of these miRNAs was associated with various biological pathways including platelet activation, calcium signalling and vascular smooth muscle contraction pathways. A significantly higher expression of miR-126-3p and miR-182-5p in hypertensives (both screen-detected and known hypertension) was observed, although the expression of miR-30a-5p, 30e-3p and 1299 was not significantly different in screen-detected hypertensives (not on therapy) when compared to the normotensives. There was a significant association between the expression of miR-126-3p, 182-5p and 30a-5p with screen-detected and known hypertension, even after adjustment for age, sex, body mass index (BMI), glycated haemoglobin (HbA1c), triglycerides (TG) and total cholesterol (TC). MiR-novel-chr1_36178 expression significantly differed by sex and only at greater levels of expression was it associated with systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP). Additionally, at higher levels of expression of the novel miRNA, there was an increased likelihood of a diagnosis of screen-detected HPT being made. Conclusion: Our findings provide evidence of miRNA dysregulation in HPT in an African population and suggest that these dysregulated miRNAs, through their effects on BP regulation pathways, are involved in the pathogenesis of HPT. Owing to their differential expression according to HPT status and correlation of their expression with clinical BP parameters, these miRNAs may be targeted for diagnostic, prognostic and therapeutic purposes in HPT.
Thesis (PhD (Biomedical Sciences))--Cape Peninsula University of Technology, 2020
Keywords: MicroRNA; Hypertension -- Etiology; Hypertension -- Genetic aspects